Effects of weed management strategy on weed dynamics and its repercussion on productivity of Indian mustard (Journal of Oilseed Brassica, 2025)
A field experiment was conducted during rabi season of 2022-23, at Banda University of Agriculture and Technology, Banda, Uttar Pradesh to study the efficacy of herbicides on weed dynamics and productivity of Indian mustard [Brassica juncea (L.) Czern & Coss]. Experiment was laid out in Randomized Block Design with eight treatments and replicated four times. Experimental crop of mustard was infested with several weeds viz. Cyperus rotundus, Cynodon dactylon, Anagalis arvensis, Chenopodium album, Dacaus carota,Rumex crispus.All the cultural and herbicidal treatments effectively reduced the dry weight of weeds by 60.8-61.5 % compared to the weedy check. Weed control efficiency at 75 DAS were in the range of 36.9 to 61.5 per cent. Yield loss due to weeds recorded 24.1%, when weeds remain unmanaged in field. The highest seed yield 1.84t ha-1obtained under weed-free conditions. Among herbicides, Pendimethalin 30 EC 1000g a.i. ha 1 PE fb (Propaquizafop 5% + oxyflourfen 12% w/w EC (ready-mix) @ 875g a.i. ha-1 PoE, recorded significantly higher seed yield of 1.7 t ha-1 and net returns of Rs.73604 ha-1. The dose of propaquizafop 5% + oxyflourfen 12% w/w EC (ready-mix) @ 875g a.i. ha-1 post emergence application had phytotoxic effect on crop.